2021
DOI: 10.3390/ijerph18094847
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Frequency of Anxiety and Depression Symptoms in a Brazilian Sample during the COVID-19 Outbreak

Abstract: The COVID-19 pandemic is a public health emergency of international concern, and the main measures to contain the spread of the coronavirus causing COVID-19 were social distancing, quarantine, and self-isolation. Although these policies are effective in containing the spread of the virus, they might represent a challenge to psychological well-being, increasing levels of depressive and anxiety-related symptoms. Aims: We explored the frequency of anxiety and depression symptoms during COVID-19 restrictions and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
4
11
0
4
Order By: Relevance
“…More recent research on the virus has found COVID-19 to be associated with changes related to precautions to avoid COVID-19 infection, distress, behavioral changes, fears and concerns, and effects on opinions and beliefs and these changes are consistent with our findings [ 38 ]. In particular, other studies publishing that stress related to COVID-19 tends to be highest among females who do not have formal education are also consistent with our findings [ 39 , 40 ]. In terms of age and educational level as significantly predicted by our study, recent literature also suggests that education level, age, sex, and social condition had a significant association with knowledge about COVID-19 [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…More recent research on the virus has found COVID-19 to be associated with changes related to precautions to avoid COVID-19 infection, distress, behavioral changes, fears and concerns, and effects on opinions and beliefs and these changes are consistent with our findings [ 38 ]. In particular, other studies publishing that stress related to COVID-19 tends to be highest among females who do not have formal education are also consistent with our findings [ 39 , 40 ]. In terms of age and educational level as significantly predicted by our study, recent literature also suggests that education level, age, sex, and social condition had a significant association with knowledge about COVID-19 [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a cross-sectional survey in China, during the COVID-19 outbreak, 53.8% of respondents rated the psychological impact of the epidemic as moderate or severe, and the effect was more significant on women. The results also showed a greater psychological impact of the outbreak and higher stress levels, anxiety, and depression in students (Wang et al, 2020) but lower when compared to developing countries such as Bangladesh (Islam et al, 2020) or even Brazil (Goularte et al, 2021;Ribeiro et al, 2021b).…”
Section: Covid-19 Outbreak and Mental Healthmentioning
confidence: 84%
“…Moreover, we detected that those respondents presenting severe depression during the social distancing measures were younger, with lower resilience and with higher scores on the anxiety scores. These outcomes indicate a difficulty for younger people to cope with stressors and keep psychological distress at lower levels during this pandemic (Chen and Bonanno, 2020), possibly due to uncertainty about their future prospects (Ribeiro et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential psychological and academic impact of confinement during the COVID-19 pandemic, students' management of stress, and a possible gender modulation, among other factors, are subjects of growing interest in the most recent psychoeducational research (Ahuja et al, 2020;Cao et al, 2020;Harutyunyan et al, 2020;Rogowska et al, 2020;Ribeiro et al, 2021). There are certain disparities in the research regarding increased academic stress during the COVID-19 outbreak (Capone et al, 2020;Rogowska et al, 2020), its repercussions on the well-being of students from different cultures (Rogowska et al, 2020) and the role of gender differences (Pomerantz et al, 2002;Harutyunyan et al, 2020;Rogowska et al, 2020).…”
Section: Student Characteristics As a Factor Of Academic Stress: Gender Differencesmentioning
confidence: 99%